NLRP1 gene polymorphism rs2670660 is associated with vitiligo in the Pakistani population - Sehresh Murtaza; Nasir Masood; Maleeha Azam; Muhammad Ajmal (Molecular Biology Reports, 2026)

Bacteriophage therapy for antimicrobial-resistant, biofilm‑associated diabetic foot infection: delivery routes, phage antibiotic synergy, and practical wound‑care integration - Muhammad Irbaz; Zunaira Hamood; Summayah Shahid; Afra Ghufran; Aamir Ajmal; Iqra Rafiq (Archives of Microbiology, 2026)

Uncovering the central role of GhSPL13 in vegetative growth, root architecture, and stress responses in cotton - Sahar Sadaqat; Muhammad Awais; Muhammad Saad bin Tahir; Ramsha Ajmal; Aneela Yasmeen; Saira Azam; Naila Shahid; Ayesha Latif; Allah Bakhsh; Ruhangiz Mammadova; Abdul Qayyum Rao (Plant Science, 2026)

Scuffled bacterial cellulose with electron-rich sites: A robust adsorbent for simultaneous adsorption and reductive immobilization of toxic vanadium from aqueous solutions - Muhammad Younas; Jawad Ali; Yanan Chen; Yongjin Xiang; Ajmal Shahzad; Sajid Ullah; Jingtao Hou (Journal of Water Process Engineering, 2026)

Artificial photosynthesis of H2O2 with covalent organic frameworks: From structural design to catalytic function - Ajmal Khan; Yasser A. Alassmy; Mohammed Qasem Alfaifi; Marwan M. Abduljawad; Sultan A. Alshuhri; Irshad Ahmad; Qinyun Huang; Yuyu Liu; Muhammad Arshad (Journal of Environmental Chemical Engineering, 2026)

Comparative immune response and disease resistance against Aeromonas hydrophila in Catla catla, Labeo rohita and their intergeneric hybrids - Muhammad Ahmad; Amina Zuberi; Muhammad Noorullah; Zohaib Noor; Waqar Younas; Ajmal Hussain; Muhammad Uzair; Muhammad Kamran (Fish & Shellfish Immunology, 2026)

Retraction notice to ‘Hispolon: A natural polyphenol and emerging cancer killer by multiple cellular signaling pathways’ [Environ. Res. 190 (2020) 110017] - Ayesha Sarfraz; Azhar Rasul; Iqra Sarfraz; Muhammad Ajmal Shah; Ghulam Hussain; Nusrat Shafiq; Muqaddas Masood; Şevki Adem; Satyajit D. Sarker; Xiaomeng Li (Environmental Research, 2026)

A time adaptive weighting framework for enhanced vegetation health index based drought monitoring - Muhammad Waseem; Ali Hasan Jaffry; Mudassar Iqbal; Muhammad Ajmal; Jiaqing Xiao; Tao Yang; Pengfei Shi; Awais Naeem Sarwar (Remote Sensing Applications: Society and Environment, 2026)

Boiling for micro(nano)plastic mitigation in drinking water: Chemical interactions, potential risks, and research gaps - Abdul Qadeer; Xiang Tu; Muhammad Anis; EH. Ibrahim; Zeeshan Ajmal; Kun Wang; Xia Jiang; Weng Shuhang (Chemical Engineering Journal, 2026)

Wheat Farming Dynamics in Pothohar: From Rainfed Practices to Irrigation Systems - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
This study evaluated the dynamics of wheat yield and water productivity under various irrigation methods and farming practices in the rainfed‐to‐irrigated transitioning areas of the Pothohar region, Pakistan. Long‐term yield data (1981–2023) from the Pakistan Bureau of Statistics and farmers' field surveys were used to benchmark existing practices. The comparative performance of conventional flood irrigation (CF) and high‐efficiency irrigation systems (HEISs) was assessed through crop water productivity and simulated root‐zone water balance using the FAO AquaCrop model. The results revealed an average wheat yield of 1.34 ± 0.34 t ha −1 , showing 78% and 69% lower yields than the Punjab provincial and national averages. Irrigated areas (2.55 ± 0.29 t ha −1 ) yielded 96% more than rainfed areas (1.30 ± 0.33 t ha −1 ), underscoring the critical role of irrigation in enhancing productivity. HEIS reduced evaporation (14%) and drainage losses (17%), resulting in 18% higher water productivity (1.66 kg m −3 ) compared with CF (1.41 kg m −3 ). Root‐zone water balance analysis confirmed that HEIS improved soil moisture conservation and transpiration efficiency, making it a sustainable irrigation option for Pothohar's semi‐arid wheat systems. The study highlights inefficiencies in prevailing practices and the potential of HEIS to bridge yield gaps and improve water productivity in the region's transitioning agroecosystems.

Linking Agro‐Climatic Variability and Field Management to Wheat Yield in a Transition From Rainfed to Reservoir‐Fed Systems - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
Climate change poses increasing risks to wheat production in semiarid regions. This study examined long‐term climate trends, wheat yield variability and farmers' perceptions and adaptation in District Rawalpindi, Pakistan. Wheat‐season (November–April) climate data (1989–2019) were analysed alongside a survey of 175 farmers. The results showed a significant increase in T min (0.05°C year −1 , p = 0.03), whereas T max increased slightly but nonsignificantly. Rainfall showed a declining, nonsignificant trend. Wheat yield exhibited high interannual variability with a weak increasing trend. Regression analysis identified rainfall as a significant predictor of yield ( β = 0.002, p = 0.011), explaining 46% of yield variation, with a 1% increase in rainfall increasing yield by 0.34%. Farmers' perceptions aligned with observed trends, with most reporting declining rainfall (78%) and increasing drought frequency (70%). Perception was significantly associated with education and farming experience. Adaptation practices included improved varieties, line sowing and minimum tillage, whereas the adoption of advanced technologies remained limited. Key barriers included knowledge gaps (86%), limited access to technology, financial constraints and weak institutional support. The findings highlight rainfall variability as the primary driver of yield instability and emphasize the need for strengthened advisory services, technology access and institutional support to enhance adaptive capacity.

How Irrigation Systems and Tillage Regimes Shape Wheat Performance and Soil Water Balance in Semi‐Arid Pakistan: A Field–Modelling Approach - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
Wheat productivity in semi‐arid regions is constrained by inefficient irrigation, suboptimal tillage and poor soil water management, leading to low yields and high nonproductive water losses. However, the combined effects of irrigation systems and tillage on the soil water balance remain insufficiently quantified under field conditions. This study evaluated the interactive effects of four irrigation–sowing systems—flat‐basin broadcast under flood irrigation (FBC), flat‐basin line sowing (FLC), narrow‐bed furrow irrigation (NLF) and wide‐bed drip irrigation (WLD)—and two tillage regimes (conventional tillage, CT; no‐tillage, NT) on wheat yield, water productivity and soil water balance in the Pothohar region of Pakistan using a randomized complete block design over two seasons (2023–2024 and 2024–2025). The results showed that WLD achieved the highest grain yield (up to 7.95 t ha −1 ), exceeding FBC by > 35% while reducing irrigation water use by 34%–43%. Raised‐bed systems (NLF and WLD) reduced deep percolation losses and improved soil water retention, whereas NT enhanced water productivity by > 30%. These results demonstrate that improved irrigation–sowing systems combined with no‐tillage enhance the soil water balance by reducing nonproductive losses and increasing productive water use, thereby improving wheat productivity under water‐limited conditions.

Efficacy of Vachellia nilotica Extract-coated Urea in Maize: Field Performance and Phytochemical Basis of Urease Inhibition - Rashid Mahmood; Hina Jabeen; Muhammad Ajmal Rana; Faisal Nadeem; Ejaz Ahmed; Muhammad Bilal Chattha (Journal of Soil Science and Plant Nutrition, 2026)

Comparative Performance of Different Plants as Phytoremediators for Heavy Metals Released by Varying Density Road Traffic in District Malakand, Pakistan - Saima Ajmal; Maria Sadia; Muhammad Zahoor (Bulletin of Environmental Contamination and Toxicology, 2026)

Structure-based virtual screening, molecular dynamics and MM-PBSA/GBSA analysis for the identification of novel CDK6 inhibitors against prostate cancer - Manzoor Ahmad; Muhammad Ajmal Khan; Ashraf Ullah Khan; Sadia Butt; Yahya Khan; Amir Zeb; Nadia Bibi; Aishma Khattak; Hina Ahsan; Ajaz Ahmad; Amin Ullah (In Silico Pharmacology, 2026)

Veterinary antibiotics and antibiotic resistance genes in agroecosystems: occurrence, environmental fate, risks, and remediation strategies - Muhammad Idress; Palwasha Khan; Ajmal Khan; Sardar Khan; Muhammad Waqas; Muhammad Kamran; Zar Ali Khan (Environmental Science and Pollution Research, 2026)

Novel design of Fe0-and AC-doped hydroxyapatite-alginate composites for efficient arsenic clean-up: Mechanistic insights from batch and column tests - Behzad Murtaza; Farwah Shamshir; Muhammad Imran; Muhammad Shahid; Kifayat Ullah; Muhammad Nadeem; M. Asif Naeem; Noor Samad Shah; Jianxu Wang; Ajmal Khan; Changseok Han (Journal of Environmental Management, 2026)

Potential efficacy of insecticides and plant growth regulators against Oxycarenus hyalinipennis (Costa) during the fruiting stage of cotton (Gossypium hirsutum L.) - Muhammad Saqib Ajmal; Muhammad Farhan; Sajjad Ali; Qaiser Shakeel; Habib Ali; Ammara Riaz; Javaid Iqbal; Konul Ahmadova; Muhammad Sarmad; Muhammad Sajjad (International Journal of Tropical Insect Science, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

Dual of CaO and MgO doped highly dispersed and stable Ni on ZrO2 for CO2 methanation - Mazhar Ahmed Memon; Yuzhen Fang; Muhammad Ajmal; Muhammad Azher Hassan; Cuijuan Zhang; Yuan Liu (Fuel, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Novel efficacy of pregnane and flavonoid glycosides from Desmidorchis flava in in vivo nociceptive and inflammatory paradigms and their target prediction by cheminformatics approach - Ajmal Khan; Hamdy Kashtoh; Najeeb Ur Rehman; Muhammad Shahid; Irfan Ullah; Asaad Khalid; Afnan Jan; Sobia Ahsan Halim; Kwang-Hyun Baek; Ahmed Al-Harrasi (Natural Product Research, 2025)

Rosa moschata leaf extract modulates complete freund’s adjuvant-induced polyarthritis in Wistar rats via regulation of pro-inflammatory and inflammatory biomarkers - Amr S. Abouzied; Uzma Saleem; Maryam Farrukh; Umme Farwa; Areej M. Alsolami; Fatima A. Jaber; Tourki A. S. Baokbah; Ibrahim Aljaezi; Nouf Abdullah Alharbi; Muhammad Ajmal Shah; Ana Sanchez Silva; Norah K. Algarzae (Inflammopharmacology, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Sustainable cementless concrete reinforced with recycled steel fibers for spun-cast precast pipes: an innovative solution - Safeer Abbas; Moncef Nehdi; Ali Ahmed; Muhammad Abdullah Khan; Muhammad Mubashir Ajmal; Ammad Amir; Muhammad Zain Kashif; Qura tul Ain (Innovative Infrastructure Solutions, 2025)

Correction: Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Hybrid electrospun fibers with metal-based catalysts for zinc-air battery: Recent development and future perspectives - Mahmood ul Haq; Yongbiao Mu; Saz Muhammad; Baoxin Wu; Kejun Yan; Jiahui Luo; Zheng Li; Zhiqing Tang; Muhammad Ajmal; Wenjia Li; Lin Zeng (Chemical Engineering Journal, 2025)

USFDA Warning Letters: An Analysis of Compliance in Over-the-Counter Drug Products (2020–2024) - Pujita Konda; Sravani yerram; Mohammad Nuwaid Khader; Ramesh Joga; Muhammad NIZAM V P; Mahesh Girhe; Ajmal C S; Saurabh Srivastava (Journal of Pharmaceutical Innovation, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

Mapping mangroves land suitability using machine learning and MCDM in the Indus Delta, Pakistan - Sher Shah Hassan; Muhammad Ajmal; Muhammad Arif Goheer; Zainab Ali; Muhammad Suleman (Theoretical and Applied Climatology, 2025)

Combined Impact of Waste Water and Farm Yard Manure on Growth of Tomato (Solanum lycopersicum L.) and Soil Health: A Sustainable Agriculture Approach - Arsalan Saghir; Muhammad Sohail Akram; Shahzad Ali; Shahla Rashid; Muhammad Ajmal Farhad; Hafiz Muhammad Tayyab Khan; Syed Ayyaz javed; Mohammad Raish; Muhammad Khubaib (Journal of Soil Science and Plant Nutrition, 2025)

Unraveling Trends in USFDAs CDER-Regulated Drug Shortages (2019–2024): Causes, Patterns, and Strategic Insights for the Future - V. P. Muhammad Nizam; Sravani Yerram; C. S. Ajmal; Rajeev Singh Raghuvanshi; Saurabh Srivastava (Journal of Pharmaceutical Innovation, 2025)

Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

A Comprehensive Review on Chemical Composition and Pharmacological Properties of Rosa damascena Mill. - Arshia Shahid; Mohd. Vaseem; Md. Arshad; Mohammad Khushtar; Mohd. Afroz Ahmad; Mohd. Ajmal; Saurabh Kumar Chauhan; Abubakar; Muhammad Arif (Current Pharmacology Reports, 2025)

Role of polyphenolics in the management of rheumatoid arthritis through intracellular signaling pathways: a mechanistic review - Uzma Saleem; Maryam Farrukh; Malik Saadullah; Rida Siddique; Humaira Gul; Aqsa Ahmad; Bushra Shaukat; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Unraveling the Complexity of Alzheimer’s Disease: Insights into Etiology and Advancements in Treatment Strategies - Bakhtawar Khan; Muhammad Khalid Iqbal; Muhammad Ajmal Khan; Hamid Khan; Mubin Mustafa Kiyani; Shahid Bashir; Shao Li (Journal of Molecular Neuroscience, 2025)

Insights into Wild Medicinal Plants: Assessing Mineral Profiles in the Ojhor Valley, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Abdul Razzaq; Ghulam Jelani; Sana Wahab; Syed Nasar Shah; Nazima Wahid; Muhammad Adnan; Mohamed Farouk Elsadek; M. Ajmal Ali; Majid Iqbal (Biological Trace Element Research, 2025)

Histological analysis of petiole structure in Euphorbiaceae species for taxonomic classification - Salman Majeed; Muhammad Zafar; Mohamed S. Elshikh; M. Ajmal Ali; Mushtaq Ahmad; Asif Mir; Trobjon Makhkamov; Mohammad Athar; Sokhib Islamov; Moona Nazish; Khislat Khaydarov; Maxsuda Nizomova; et al. (Genetic Resources and Crop Evolution, 2025)

Nanoarchitectonics of molybdenum rich crown shaped polyoxometalates based ionic liquids reinforced on magnetic nanoparticles for the removal of microplastics and heavy metals from water - Hameed Ullah; Taghrid S. Alomar; Muhammad Tariq; Najla AlMasoud; Moazzam H. Bhatti; Muhammad Ajmal; Zahra Nazar; Muhammad Nadeem; Hafiz Muhammad Asif; Muhammad Sohail (Journal of Environmental Chemical Engineering, 2024)

Advances in agar-based composites: A comprehensive review - Muffarih Shah; Abdul Hameed; Muhammad Kashif; Noor Majeed; Javariya Muhammad; Nasrullah Shah; Touseef Rehan; Abbas Khan; Jalal Uddin; Ajmal Khan; Hamdy Kashtoh (Carbohydrate Polymers, 2024)

Comparative analysis of mechanical characteristics in masonry walls: impact of aspect ratios and opening percentages - Ubaid Ahmad Mughal; Asad Ullah Qazi; Ali Ahmed; Umbreen Us Sahar; Muhammad Mubashir Ajmal (European Journal of Environmental and Civil Engineering, 2024)

Enhancing degradation of PLA-made rigid biodegradable plastics with non-thermal plasma treatment - Muhammad Ajmal; Muhammad Asad; Weizhong Huo; Yuchao Shao; Wenjing Lu (Journal of Cleaner Production, 2024)

Proximate composition and prevalence and exposure assessment of aflatoxins intake through consumption of fresh carrot and processed marketed carrot products in South Punjab, Pakistan - Aneela Nijabat; Shahwana Bibi; Maryam Ajmal; Saher Nawaz; Muhammad Zaheer Sajid; Saad Ullah Khan Leghari; Muhammad Mahmood-ur-Rehman; Naima Huma Naveed; Aamir Ali; Philipp W. Simon (Natural Product Research, 2024)

Deciphering the future of electric vehicles amid emissions and adoption drivers - Khalid Mehmood; Xuchun Qiu; Abdul Ghaffar; Muhammad Ajmal Khan (Ambio, 2024)

Flexible MXenes for printing energy storage devices - Iftikhar Hussain; Onkar Jaywant Kewate; Sumanta Sahoo; Sikandar Aftab; P. Rosaiah; Muhammad Ahmad; Muhammad Bilal Hanif; Wail Al Zoubi; Zeeshan Ajmal; Waqas Ul Arifeen; Mohd Zahid Ansari; Bhargav Akkinepally; et al. (Chemical Engineering Journal, 2024)

An integrated land change modeler and distributed hydrological model approach for quantifying future urban runoff dynamics - Asad Hussain Muhammad; Waseem Muhammad; Ajmal Muhammad; Atiq Ur Rehman Tariq Muhammad; Jiaqing Xiao; Tao Yang; Pengfei Shi (Science China Earth Sciences, 2024)

Ensuring Product Safety: A Comprehensive Retrospective Study of USFDA Drug Recalls (2019–2023) - Muhammad Nizam VP; Sravani Yerram; Jayasri Devi Patnam; Ajmal CS; Gayatri Aglave; Ramesh Joga; Rajeev Singh Raghuvanshi; Saurabh Srivastava (Journal of Pharmaceutical Innovation, 2024)

Temporal assessment of forest cover dynamics in response to forest fires and other environmental impacts using AI - Shehla Noor; Rafia Mumtaz; Muhammad Ajmal Khan (Environmental Monitoring and Assessment, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Proactive Approaches to cGMP Compliance: Insights and Key Takeaways from USFDA Warning Letters to Pharmaceutical Industries Between 2019 and 2024 - Gayatri Aglave; Sravani Yerram; Jayasri Devi Patnam; C. S. Ajmal; V. P. Muhammad Nizam; Ramesh Joga; Rajeev Singh Raghuvanshi; Saurabh Srivastava (Journal of Pharmaceutical Innovation, 2024)

Investigation of torsion in confined masonry structures originating due to unsymmetric openings - Ubaid Ahmad Mughal; Asad Ullah Qazi; Ali Ahmed; Muhammad Mubashir Ajmal; Muhammad Danish (European Journal of Environmental and Civil Engineering, 2024)

Genotoxicity of Copper, Silver and Green Synthetic Gold Nanoparticles in Fish (Ctenopharyngodon idella) - Ajmal Khan; Maghfoor Khan; Nazish Shah; Mansoor Khan; Abidullah Dawar; Ashraf Ali Shah; Farmanullah Dawar; Muhammad Khisroon (Biological Trace Element Research, 2024)

Integrating FinTech with Industry 4.0 for sustainable mineral resource management: Exploring the interplay of technology, regulation, and economic dynamics - Imran Khan; Inayat Khan; Rana Muhammad Adnan Ikram; Mohammad Ajmal Ali (Resources Policy, 2024)

Redirecting surface reconstruction of CoP-Cu heterojunction to promote ammonia synthesis at industrial-level current density - Li Gan; Xiaoxue Zhang; Lei Guo; Muhammad Ajmal; Ru Jia; Xiaolei Guo; Chengxiang Shi; Lun Pan; Faryal Idrees; Xiangwen Zhang; Zhen-Feng Huang; Guidong Yang; et al. (Chemical Engineering Journal, 2024)

Enhanced Food Waste Chain Elongation for Caproate Production: Role of Inorganic Carbon and Optimization Strategies - Weizhong Huo; Tong Hu; Yuchao Shao; Rong Ye; Ajmal Muhammad; Wenjing Lu (Resources, Conservation and Recycling, 2024)

Deforestation detection and reforestation potential due to natural disasters—A case study of floods - Muhammad Hassan Maqsood; Rafia Mumtaz; Muhammad Ajmal Khan (Remote Sensing Applications: Society and Environment, 2024)

High strength rubberized porous concrete for sustainable pavements: Engineering properties and life cycle assessment - Musa Ajmal Khan; Junaid Ahmad; Hammad Anis Khan; Muhammad Umer (Journal of Cleaner Production, 2024)

Unveiling the green horizon: A bibliometric analysis of global foreign direct investment research and its emphasis on climate change - Muhammad Shabbar Raza; Yusheng Wang; Abdul Rauf; Noshaba Aziz; Muhammad Ajmal Khan; Abid Hussain (Journal of Cleaner Production, 2024)

Deep-dewatering of sewage sludge using double dielectric barrier discharge (DDBD) plasma technology - Muhammad Ajmal; Yuchao Shao; Weizhong Huo; Wenjing Lu (Science of The Total Environment, 2024)

Characteristics of unconfined masonry walls under in-plane static and reverse-cyclic loading: a comparative numerical study - Muhammad Asad Naseer; Asad Ullah Qazi; Ubaid Ahmad Mughal; Muhammad Mubashir Ajmal; Ali Ahmed (European Journal of Environmental and Civil Engineering, 2024)

Advances/Scope and prospects of g-C3N4 derived fascinating photocatalyst as a leading route towards solar energy adaption - Asif Hayat; Muhammad Sohail; Zeeshan Ajmal; Hala H. Abd El-Gawad; Djamel Ghernaout; Yas Al-Hadeethi; Saleem Raza; Yasin Orooji (Journal of Cleaner Production, 2024)

Microbial diversity and potential health risks of household municipal solid waste in China: A case study in winter during outbreak of COVID-19 - Yanqing Liu; Shuang Li; Zelin Zheng; Xiangyu Zheng; Muhammad Ajmal; Ming Zhao; Wenjing Lu (Science of The Total Environment, 2023)

Curcuminoids-enriched extract and its cyclodextrin inclusion complexes ameliorates arthritis in complete Freund’s adjuvant-induced arthritic mice via modulation of inflammatory biomarkers and suppression of oxidative stress markers - Uzma Saleem; Zunera Chauhdary; Zunaira Bakhtawar; Jawaher Alqahtani; Maryam Farrukh; Ifat Alsharif; Tourki A. S. Baokbah; Muhammad Ajmal Shah; Renald Blundell; Pharkphoom Panichayupakaranant (Inflammopharmacology, 2023)

Titanium doped cobalt ferrite fabricated graphene oxide nanocomposite for efficient photocatalytic and antibacterial activities - Kiran Khalid; Anam Zahra; Umay Amara; Muhammad Khalid; Muhammad Hanif; Mubashir Aziz; Khalid Mahmood; Muhammad Ajmal; Muhammad Asif; Kinza Saeed; Muhammad Farooq Qayyum; Waseem Abbas (Chemosphere, 2023)

Enhanced production of hydrothermal humic acid in a two-step hydrothermal process with acid hydrothermal solution recycling - Yuchao Shao; Zhangrui Luo; Menggang Bao; Weizhong Huo; Rong Ye; Muhammad Ajmal; Wenjing Lu (Chemical Engineering Journal, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Multiplex Cas9-based excision of CLCuV betasatellite and DNA-A revealed reduction of viral load with asymptomatic cotton plants - Sana Shakoor; Abdul Qayyum Rao; Sara Ajmal; Aneela Yasmeen; Muhammad Azmat Ullah Khan; Sahar Sadaqat; Naeem Mahmood Ashraf; Felix Wolter; Michael Pacher; Tayyab Husnain (Planta, 2023)

Administration of α-lipoic acid and silymarin attenuates aggression by modulating endocrine, oxidative stress and inflammatory pathways in mice - Adnan Karim; Fareeha Anwar; Uzma Saleem; Saniya Fatima; Tariq Ismail; Ahmad J. Obaidullah; Rana O. Khayat; Moneerah J. Alqahtani; Ifat Alsharif; Haroon Khan; Celia Vargas-De-La-Cruz; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Highly energy-efficient and safe-environment-friendly ultra short electrical arc machining for titanium alloy: Mechanism, characteristics, and parameter estimation - Dan Song; Kai Liu; Muhammad Ajmal Khan; Hu Luo; Li Zhang; Zongjie Zhou; Jianbo Zhang; Beenish Bashir; Jianping Zhou (Journal of Cleaner Production, 2023)

Unlocking the potential of humic acid production through oxygen-assisted hydrothermal humification of hydrochar - Yuchao Shao; Yiqi Geng; Zhihua Li; Yuyang Long; Muhammad Ajmal; Wenjing Lu; Jun Zhao (Chemical Engineering Journal, 2023)

Ginsenosides in cancer: Targeting cell cycle arrest and apoptosis - Muhammad Ajmal Shah; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Momna Bilal; Rimsha Yousaf; Roaa Mohammed Tahir Kassim; Azhar Rasul; Uzma Saleem; Maria Silvana Alves; Haroon Khan; Renald Blundell; et al. (Chemico-Biological Interactions, 2023)

Bifunctional electrocatalytic water splitting augmented by cobalt-nickel-ferrite NPs-supported fluoride-free MXene as a novel electrocatalyst - Tabinda Rasheed; Aamir Rasheed; Fatimah Mohammed A. Alzahrani; Sara Ajmal; Muhammad Farooq Warsi; M.S. Al-Buriahi; Ghulam Dastgeer; Seung Goo Lee (Fuel, 2023)

Biochemical profiling of berberine-enriched extract in aluminum chloride induced oxidative damage and neuroinflammation - Muhammad Sajid Hamid Akash; Moazzama Akbar; Kanwal Rehman; Muhammad Ajmal Shah; Pharkphoom Panichayupakaranant; Muhammad Imran; Mohammed A. Assiri (Environmental Science and Pollution Research, 2023)

Genotoxic effects of polycyclic aromatic hydrocarbons (PAHs) present in vehicle-wash wastewater on grass carp (Ctenopharyngodon idella) and freshwater mussels (Anodonta cygnea) - Sardar Khan; Zahir Qamar; Ajmal Khan; Muhammad Waqas; Javed Nawab; Muhmmmad Khisroon; Ajmal Khan (Environmental Pollution, 2023)

Correction to: Spatiotemporal assessment of the hydrometeorology in a transboundary Kabul River Basin - Mahmood Alam Khan; Muhammad Shahzad Khattak; Muhammad Ajmal; Taj Ali Khan (Arabian Journal of Geosciences, 2023)

Mining therapeutic targets from the antibiotic-resistant Campylobacter coli and virtual screening of natural product inhibitors against its riboflavin synthase - Khurshid Jalal; Kanwal Khan; Ajmal Hayat; Diyar Ahmad; Ghallab Alotaibi; Reaz Uddin; Mutaib M. Mashraqi; Ahmad Alzamami; Muhammad Aurongzeb; Zarrin Basharat (Molecular Diversity, 2023)

Spatiotemporal assessment of the hydrometeorology in a transboundary Kabul River Basin - Mahmood Alam Khan; Muhammad Shahzad Khattak; Muhammad Ajmal; Taj Ali Khan (Arabian Journal of Geosciences, 2023)

The curative and mechanistic acumen of curcuminoids formulations against haloperidol induced Parkinson’s disease animal model - Uzma Saleem; Sundas Khalid; Zunera Chauhdary; Fareeha Anwar; Muhammad Ajmal Shah; Ifat Alsharif; Ahmad O. Babalghith; Rana O. Khayat; Aishah E. Albalawi; Tourki A. S. Baokbah; Maryam Farrukh; Celia Vargas-De-La-Cruz; et al. (Metabolic Brain Disease, 2023)

The versatility of nanocellulose, modification strategies, and its current progress in wastewater treatment and environmental remediation - Ajmal Shahzad; Muhammad Wajid Ullah; Jawad Ali; Kazim Aziz; Muhammad Asif Javed; Zhijun Shi; Sehrish Manan; Mazhar Ul-Islam; Mudasir Nazar; Guang Yang (Science of The Total Environment, 2023)

Development and testing of updated curve number models for efficient runoff estimation in steep-slope watersheds - Muhammad Ajmal; Muhammad Waseem; Muhammad Jehanzaib; Tae-Woong Kim (Journal of Hydrology, 2023)

Hydrothermal humification of lignocellulosic components: Who is doing what? - Yuchao Shao; Weizhong Huo; Rong Ye; Yanqing Liu; Muhammad Ajmal; Wenjing Lu (Chemical Engineering Journal, 2023)

Sarcococca saligna ameliorated D-galactose induced neurodegeneration through repression of neurodegenerative and oxidative stress biomarkers - Uzma Saleem; Zunera Chauhdary; Sumera Islam; Aimen Zafar; Rana O. Khayat; Norah A. Althobaiti; Ghulam Mujtaba Shah; Mohammed Alqarni; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Antidepressant activity of phytochemicals of Mangifera indica seeds assisted by integrated computational analysis - Uzma Saleem; Shafa Iman; Bashir Ahmad; Muhammad Ajmal Shah; Shabana Bibi; Mohammed Alqarni; Muhammad Saad Khan; Ghulam Mujtaba Shah; Haroon Khan; Reem Hasaballah Alhasani; Norah A. Althobaiti; Aishah E. Albalawi (Metabolic Brain Disease, 2023)

CRISPR/Cas9-mediated genome editing in diploid and tetraploid potatoes - Aneela Yasmeen; Allah Bakhsh; Sara Ajmal; Momna Muhammad; Sahar Sadaqat; Muhammad Awais; Saira Azam; Ayesha Latif; Naila Shahid; Abdul Qayyum Rao (Acta Physiologiae Plantarum, 2023)

MoS4-LDH: A dual centre Fe-based layered double hydroxide catalyst for efficient atrazine removal and peroxymonsulfate activation - Jawad Ali; Dan Li; Ajmal Shahzad; Muhammad Wajid Ullah; Jerosha Ifthikar; Muhammed Asif; Chen Yanan; Xie Lei; Zhuqi Chen; Songlin Wang (Chemical Engineering Journal, 2023)

From biomass to humic acid: Is there an accelerated way to go? - Yuchao Shao; Menggang Bao; Weizhong Huo; Rong Ye; Muhammad Ajmal; Wenjing Lu (Chemical Engineering Journal, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Consistent choice for cohesion and internal friction for concrete constitutive models - Muhammad Ajmal; Danish Ahmed; Mohammed H. Baluch; Muhammad K. Rahman; Tahar Ayadat (Innovative Infrastructure Solutions, 2023)

Differential neuroprotective effect of curcuminoid formulations in aluminum chloride–induced Alzheimer’s disease - Anam Shabbir; Kanwal Rehman; Muhammad Sajid Hamid Akash; Moazzama Akbar; Zunera Chaudhary; Pharkphoom Panichayupakaranant; Muhammad Ajmal Shah (Environmental Science and Pollution Research, 2022)

The impact of COVID-19 pandemic on air pollution: a global research framework, challenges, and future perspectives - Khalid Mehmood; Sana Mushtaq; Yansong Bao; Saifullah; Sadia Bibi; Muhammad Yaseen; Muhammad Ajmal Khan; Muhammad Mohsin Abrar; Zaid Ulhassan; Shah Fahad; George P. Petropoulos (Environmental Science and Pollution Research, 2022)

Validation of in vitro grafting using indigenous wild grapevines as rootstock with commercial scion varieties - Fahad Nazir; Touqeer Ahmad; Muhammad Ajmal Bashir; Rizwan Rafique; Irfan Ali; Cristian Silvestri; Eddo Rugini; Sadar Uddin Siddiqui (Acta Physiologiae Plantarum, 2022)

Meteorological trend analysis for Najd and Hejaz regions, Saudi Arabia - Ateeq-ur-Rauf; Navid Ahmad; Muhammad Ajmal; Abdul Malik; Zia ur Rahman (Meteorology and Atmospheric Physics, 2022)

Sarcococca saligna extract attenuates formaldehyde-induced arthritis in Wistar rats via modulation of pro-inflammatory and inflammatory biomarkers - Maryam Farrukh; Uzma Saleem; Muhammad Qasim; Maria Manan; Muhammad Ajmal Shah (Inflammopharmacology, 2022)

Ameliorative effect of ethoxylated chalcone-based MAO-B inhibitor on behavioural predictors of haloperidol-induced Parkinsonism in mice: evidence of its antioxidative role against Parkinson’s diseases - Naseer Maliyakkal; Uzma Saleem; Fareeha Anwar; Muhammad Ajmal Shah; Bashir Ahmad; Filzah Umer; Mohammad Ali Abdullah Almoyad; Della Grace Thomas Parambi; Asmy Appadath Beeran; Lekshmi R Nath; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

Tick-borne Diseases in Sheep and Goats in Pakistan: A Systematic Review and Meta-analysis - Aqsa Mushtaq; Tehniat Shoukat; Tanzila Mumtaz; Muhammad Qasim; Kiran Ajmal; Nayab Fatima; Aisha Khan; Misbah Kouser; Nazeer Hussain; Sadia Selim Khan; Mohammed Sohail Afzal; Sami Simsek; et al. (Acta Parasitologica, 2021)

Evaluation of the allelopathic effects of leachate from an invasive species (Wedelia triobata) on its own growth and performance and those of a native congener (W. chinensis) - Muhammad Saif Ullah; Jianfan Sun; Susan Rutherford; Ikram Ullah; Qaiser Javed; Ghulam Rasool; Muhammad Ajmal; Daolin Du (Biological Invasions, 2021)

Photosynthetic Activities and Photosynthetic Nitrogen Use Efficiency of Maize Crop Under Different Planting Patterns and Nitrogen Fertilization - Jamal Nasar; Waqif Khan; Muhammad Zubair Khan; Harun Ireri Gitari; Jones Feyisike Gbolayori; Abdourazak Alio Moussa; Ajmal Mandozai; Nabeel Rizwan; Gulaqa Anwari; Sami Muhammad Maroof (Journal of Soil Science and Plant Nutrition, 2021)

Antiparkinsonian activity of Cucurbita pepo seeds along with possible underlying mechanism - Uzma Saleem; Aisha Shehzad; Shahid Shah; Zohaib Raza; Muhammad Ajmal Shah; Shabana Bibi; Zunera Chauhdary; Bashir Ahmad (Metabolic Brain Disease, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

Neuroprotective potential of Malva neglecta is mediated via down-regulation of cholinesterase and modulation of oxidative stress markers - Uzma Saleem; Rubina Akhtar; Fareeha Anwar; Muhammad Ajmal Shah; Zunera Chaudary; Muhammad Ayaz; Bashir Ahmad (Metabolic Brain Disease, 2021)

Socioeconomic impacts of domestic biogas plants on rural households to strengthen energy security - Nadeem Iqbal; Muhammad Arshad Sakhani; Abdul Razzaq Khan; Atiq-ur-Rehman; Zahid Ajmal; Muhammad Zubair Khan (Environmental Science and Pollution Research, 2021)

Scalp Hair Metal Analysis Concerning DNA Damage in Welders of Peshawar Khyber Pakhtunkhwa Pakistan - Muhammad Khisroon; Ajmal Khan; Ashraf Ali Shah; Ihsan Ullah; Javeed Farooqi; Abid Ullah (Biological Trace Element Research, 2021)

Projected drought pattern under climate change scenario using multivariate analysis - Muhammad Waseem; Muhammad Ajmal; Ijaz Ahmad; Noor Muhammad Khan; Muhammad Azam; Muhammad Kaleem Sarwar (Arabian Journal of Geosciences, 2021)

Assessment of DNA damage induced by endosulfan in grass carp (Ctenopharyngodon idella Valenciennes, 1844) - Muhammad Khisroon; Nazia Hassan; Ajmal Khan; Javeed Farooqi (Environmental Science and Pollution Research, 2021)

Biology-oriented drug synthesis (BIODS), in vitro urease inhibitory activity, and in silico studies on ibuprofen derivatives - Faiza Seraj; Kanwal; Khalid Mohammed Khan; Ajmal Khan; Muhammad Ali; Ruqaiya Khalil; Zaheer Ul-Haq; Shehryar Hameed; Muhammad Taha; Uzma Salar; Shahnaz Perveen (Molecular Diversity, 2021)

Growth regulation of Desmostachya bipinnata by organ-specific biomass, water relations, and ion allocation responses to improve salt resistance - Muhammad Yousuf Adnan; Tabassum Hussain; Muhammad Zaheer Ahmed; Bilquees Gul; M. Ajmal Khan; Brent L. Nielsen (Acta Physiologiae Plantarum, 2021)

Dihydropyrimidones: A ligands urease recognition study and mechanistic insight through in vitro and in silico approach - Farman Ali Khan; Shahbaz Shamim; Nisar Ullah; Muhammad Arif Lodhi; Khalid Mohammed Khan; Kanwal; Farman Ali; Sahib Gul Afridi; Shahnaz Perveen; Ajmal Khan (Medicinal Chemistry Research, 2021)

Genotoxic Consequences in Common Grass Carp (Ctenopharyngodon idella Valenciennes, 1844) Exposed to Selected Toxic Metals - Nazish Shah; Ajmal Khan; Nazma Habib Khan; Muhammad Khisroon (Biological Trace Element Research, 2021)

Modeling smallholder livestock herders’ intentions to adopt climate smart practices: An extended theory of planned behavior - Muhammad Faisal; Xia Chunping; Shoaib Akhtar; Muhammad Haseeb Raza; Muhammad Tariq Iqbal Khan; Muhammad Arslan Ajmal (Environmental Science and Pollution Research, 2020)

Toxicity evaluation of pesticide chlorpyrifos in male Japanese quails (Coturnix japonica) - Suliman; Ajmal Khan; Syed Sajjad Ali Shah; Naila Gulfam; Muhammad Khisroon; Muhammad Zahoor (Environmental Science and Pollution Research, 2020)

Phytotoxic analysis of coastal medicinal plants and quantification of phenolic compounds using HPLC - Muhammad Qasim; Yoshiharu Fujii; Muhammad Zaheer Ahmed; Irfan Aziz; Kazuo N. Watanabe; M. Ajmal Khan (Plant Biosystems, 2019)

Oxindole-based chalcones: synthesis and their activity against glycation of proteins - Ayesha Khan; Ajmal Khan; Umar Farooq; Muhammad Taha; Syed Adnan Ali Shah; Sobia Ahsan Halim; Arfa Akram; Mohammed Ziauddin Khan; Abdul Khaliq Jan; Ahmed Al-Harrasi (Medicinal Chemistry Research, 2019)

Homotypic Clusters of Transcription Factor Binding Sites in the First Large Intron of AGL24 MADS-Box Transcription Factor Are Recruited in the Enhancement of Floral Expression - Tajammul Hussain; Nazia Rehman; Safeena Inam; Wajya Ajmal; Amber Afroz; Aish Muhammad; Yusuf Zafar; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Plant Molecular Biology Reporter, 2019)

Modeling Sugar Beet Response to Different Combinations of On-Farm Water Management Practices Under Semi-arid Sub-tropical Environment - Abdul Malik; Abdul Sattar Shakir; Muhammad Jamal Khan; Muhammad Ajmal; Muhammad Shahzad Khattak; Taj Ali Khan; Zia Ul Haq; Mahmood Alam Khan; Naeem Ijaz (Sugar Tech, 2019)

Bioaccumulation of Heavy Metals and their Genotoxic Effect on Freshwater Mussel - Muhammad Iftikhar Khan; Muhammad Zahoor; Ajmal Khan; Naila Gulfam; Muhammad Khisroon (Bulletin of Environmental Contamination and Toxicology, 2019)

Performance Evaluation of the Raised-Bed Planting and Potential in Improving Sugar Beet Yield and Water Use Efficiency in Pakistan - Abdul Malik; Abdul Sattar Shakir; Muhammad Latif; Muhammad Ajmal (Sugar Tech, 2018)

Bio-monitoring of Tissue Accumulation and Genotoxic Effect of Heavy Metals in Cyprinus carpio from River Kabul Khyber Pakhtunkhwa Pakistan - Muhammad Siraj; Muhammad Khisroon; Ajmal Khan; Farrah Zaidi; Ahmad Ullah; Ghani Rahman (Bulletin of Environmental Contamination and Toxicology, 2018)

Assessment of AquaCrop Model in Simulating Sugar Beet Canopy Cover, Biomass and Root Yield under Different Irrigation and Field Management Practices in Semi-Arid Regions of Pakistan - Abdul Malik; Abdul Sattar Shakir; Muhammad Ajmal; Muhammad Jamal Khan; Taj Ali Khan (Water Resources Management, 2017)

Differences in photosynthetic syndromes of four halophytic marsh grasses in Pakistan - Muhammad Moinuddin; Salman Gulzar; Abdul Hameed; Bilquees Gul; M. Ajmal Khan; Gerald E. Edwards (Photosynthesis Research, 2017)

Synthesis and urease inhibitory activities of benzophenone semicarbazones/thiosemicarbazones - Arshia Arshia; Ajmal Khan; Khalid Mohammed Khan; Syed Muhammad Saad; Nida Iqbal Siddiqui; Sumaira Javaid; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Comparative enzyme inhibition study of 1-deazapurines - Iftikhar Ali; Ajmal Khan; Amjad Hussain; Umar Farooq; Muhammad Ismail; Viqar Hyder; Viqar U. Ahmad; Viktor O. Iaroshenko; Hidayat Hussain; Peter Langer (Medicinal Chemistry Research, 2016)

Multivariate Drought Assessment Considering the Antecedent Drought Conditions - Muhammad Waseem; Muhammad Ajmal; Joo Heon Lee; Tae-Woong Kim (Water Resources Management, 2016)

Bioaccumulation of Heavy Metals in Different Organs of Wallago attu from River Kabul Khyber Pakhtunkhwa, Pakistan - Muhammad Siraj; Muhammad Khisroon; Ajmal Khan (Biological Trace Element Research, 2016)

Stability assessment of the curve number methodology used to estimate excess rainfall in forest-dominated watersheds - Muhammad Ajmal; Tae-Woong Kim; Jae-Hyun Ahn (Arabian Journal of Geosciences, 2016)

Excess Stormwater Quantification in Ungauged Watersheds Using an Event-Based Modified NRCS Model - Muhammad Ajmal; Jae-Hyun Ahn; Tae-Woong Kim (Water Resources Management, 2016)

Benzamide sulfonamide derivatives: potent inhibitors of carbonic anhydrase-II - Muhammad Saleem; Aamer Saeed; Atia-tul-Wahab; Ajmal Khan; Sanaullah Abbasi; Waqasuddin Khan; Sher Bahadar Khan; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

A new rosane-type diterpenoid from Stachys parviflora and its density functional theory studies - Umar Farooq; Khurshid Ayub; Muhammad Ali Hashmi; Rizwana Sarwar; Afsar Khan; Mumtaz Ali; Manzoor Ahmad; Ajmal Khan (Natural Product Research, 2015)

WsMAGO2, a duplicated MAGO NASHI protein with fertility attributes interacts with MPF2-like MADS-box proteins - Humera Ihsan; Muhammad Ramzan Khan; Wajya Ajmal; Ghulam Muhammad Ali (Planta, 2015)

Improved Runoff Estimation Using Event-Based Rainfall-Runoff Models - Muhammad Ajmal; Muhammad Waseem; Jae-Hyun Ahn; Tae-Woong Kim (Water Resources Management, 2015)

Variability of aerosol optical depth over Swat in Northern Pakistan based on satellite data - Khan Alam; Rehana Khan; Shahid Ali; Muhammad Ajmal; Gulzar Khan; Wazir Muhammad; Malak Azmat Ali (Arabian Journal of Geosciences, 2015)

2-(2′-Pyridyl) benzimidazole derivatives and their urease inhibitory activity - Zafar Saeed Saify; Arfa Kamil; Shamim Akhtar; Muhammad Taha; Ajmal Khan; Khalid Mohammed Khan; Sarwat Jahan; Fazal Rahim; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2014)

Antiproliferative effects of novel urea derivatives against human prostate and lung cancer cells; and their inhibition of β-glucuronidase activity - Shahnaz Perveen; Sana Mustafa; Kehkashan Qamar; Ahsana Dar; Khalid M. Khan; Muhammad Iqbal Choudhary; Ajmal Khan; Wolfgang Voelter (Medicinal Chemistry Research, 2014)

Novel and recurrent LDLR gene mutations in Pakistani hypercholesterolemia patients - Waqas Ahmed; Muhammad Ajmal; Ahmed Sadeque; Roslyn A. Whittall; Sobia Rafiq; Wendy Putt; Athar Khawaja; Fauzia Imtiaz; Nuzhat Ahmed; Maleeha Azam; Steve E. Humphries; Raheel Qamar (Molecular Biology Reports, 2012)

Role of tissue plasminogen activator and plasminogen activator inhibitor polymorphism in myocardial infarction - Waqas Ahmed; Meera Malik; Imran Saeed; Amina Ali Khan; Ahmed Sadeque; Umar Kaleem; Nuzhat Ahmed; Muhammad Ajmal; Maleeha Azam; Raheel Qamar (Molecular Biology Reports, 2011)

Identification of a recurrent insertion mutation in the LDLR gene in a Pakistani family with autosomal dominant hypercholesterolemia - Muhammad Ajmal; Waqas Ahmed; Ahmed Sadeque; Syeda Hafiza Benish Ali; Syed Habib Bokhari; Nuzhat Ahmed; Raheel Qamar (Molecular Biology Reports, 2010)